Occurrence, source apportionment, and ecological risk assessment of organophosphate esters in surface sediment from the Ogun and Osun Rivers, Southwest Nigeria - Muideen Remilekun Gbadamosi; Adeyemi Lawrence Ogunneye; David Olaoluwa Jegede; Mohamed Abou-Elwafa Abdallah; Stuart Harrad (Environmental Science and Pollution Research, 2023)
Organophosphate esters (OPEs) are synthetic chemicals widely used as e.g., flame retardants and plasticisers in various consumer products. Due to the toxicity of OPEs in aquatic ecosystems, exposure of fauna and flora to these compounds is of potential concern. In this study, the concentrations, profiles, sources, and ecological risk of eight OPEs were investigated in the sediments from the two major rivers in southwest Nigeria. Concentrations of ∑OPEs in surface sediments were in the range 13.1 – 2110 ng/g dry weight (dw) (median: 378 ng/g dw) in the Ogun River and 24.7—589 ng/g dw (median: 174 ng/g dw) in the Osun River. These concentrations are broadly within the range of those reported in surface sediment in previous studies conducted in other locations around the world. Tris (2-butoxyethyl) phosphate (TBOEP) was the dominant OPE in the sediment samples with a median concentration of 337 and 126 ng/g dw for the Ogun and Osun Rivers respectively, while tri-n-butyl phosphate (TnBP) was not detected in any sample. Excluding TBOEP, the chlorinated organophosphate esters: tris(2-chloroethyl) phosphate (TCEP), tris(2-chloro-propyl) phosphate (TCIPP), and tris(1,3-dichloro-2-propyl) phosphate (TDCIPP) were the dominant OPEs in the Osun River, while the aryl-OPEs: triphenyl phosphate (TPHP), 2-ethylhexyl diphenyl phosphate (EHDPP), and tri- m -tolyl phosphate (TMTP) were dominant in the Ogun River. Under a median exposure scenario, moderate ecological risk was predicted from exposure to TCIPP in the Osun River. In contrast, under a high exposure scenario, concentrations of TDCIPP (risk quotient, RQ = 5.33—5.37) constituted a high ecological risk in both rivers, with moderate risks observed for TBOEP (RQ = 0.022—0.18) and TCIPP (RQ = 0.097 – 0.16). Therefore, the risk to aquatic organisms from concomitant exposure to mixtures of OPEs in freshwater ecosystems requires further investigation. Graphical Abstract